Investigation on the factors leading to abnormal shrinkage percentages at branch especially Bon Marche and company level, case study: OK Zimbabwe Limited. - Zhou, Dionie (Midlands Satate university, 2014)
The research study sought to investigate on the factors leading to abnormal shrinkage percentages at branch and company level. A significant rise in the shrinkage percentages of OK Zimbabwe Limited especially the Bon Marche branches led to the initiation of the study. The main research objectives were to examine the drivers of shrinkage and to come up with strategies that may be employed to manage abnormal shrinkages. Accredited scholars and journals were used to gain explicit understanding of the topic under review. The global outlook of shrinkages enabled the researcher to view OK Zimbabwe as a world class retailer and how it stands. A case study descriptive design was used to carry out the research. Interviews and questionnaires were employed as research instruments for primary data collection. The authenticity of the questionnaires was 97.4% and a 100% from the interviews after administering a sample of 38 questionnaires and conducting 5 interviews. Tables, graphs, pie charts, descriptive explanatory notes and interview summary were adopted for the presentation and analysis of data. The results revealed that a significant percentage of abnormal shrinkages were caused by employee theft followed by customer theft, administrative errors and supplier fraud. It was recommended that OK Zimbabwe Limited should view shrinkage as a people, process and technical challenge where a holistic approach should be employed by involving all departments within the organisation towards tackling abnormal shrinkages.